Synthesis Identification of the New Heterocyclic System from Lactam - Ali, suad M.; ALsahib, Sanaa A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The importance of heterocyclic compounds has long been recognized, and the use of chemicals has remained constant, including in the manufacturing of pharmaceuticals. Several lactam synthesis methods have been developed. Among the essential compounds in our lives are lactams from amines and aldehydes and the preparation of Schiff bases. Schiff bases are prepared in two ways, including the reaction of hydrazine and various aldehydes with tetraethylamine and the production of a Schiff base, which leads to the formation of two types of lactams and the preparation of a kind of reaction of different amines and aldehydes. Three techniques prepared the lactams, the first being Schiff bases with acetyl chloride and triethylamine as catalysts and using dioxane as the solvent; The second is from Schiff bases with carboxylic acids; The third is aldehydes with amines. It produces beta-lactam derivatives (azetidine), and this research focuses on the production of lactams and their polymerization through their reaction with ethanol once and with ethanol and the base to form industrial polymers, which are polymers that are produced in the form of a final product with an active end and are used in many industries. These polymers have moderate to high antioxidant activity, and after being treated with safer natural materials, they are environmentally friendly compared to other materials. Its chemical composition was evaluated by the following required tests (FTIR, HNMR).